2021
DOI: 10.3389/fphar.2020.599965
|View full text |Cite
|
Sign up to set email alerts
|

The Breast Cancer Stem Cells Traits and Drug Resistance

Abstract: Drug resistance is a major challenge in breast cancer (BC) treatment at present. Accumulating studies indicate that breast cancer stem cells (BCSCs) are responsible for the BC drugs resistance, causing relapse and metastasis in BC patients. Thus, BCSCs elimination could reverse drug resistance and improve drug efficacy to benefit BC patients. Consequently, mastering the knowledge on the proliferation, resistance mechanisms, and separation of BCSCs in BC therapy is extremely helpful for BCSCs-targeted therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 297 publications
0
45
0
Order By: Relevance
“…Secondly, we found higher mRNA levels of EMT (vimentin, MMP9, CD44, ICAM1, SNAI1, SNAI2, TNFRS11B)- and CSC (ABCG2, OCT4, Nanog, Musashi)-related mRNAs (Fig. 4E ), all shown to contribute a clonogenic, chemo-resistant phenotype in MPM and other solid tumors [ 40 , 41 ]. Finally, we found increased mRNA of enzymes involved in downstream processing of AA, namely PGES, PTGIS, COX1 and COX2 [ 42 ](Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Secondly, we found higher mRNA levels of EMT (vimentin, MMP9, CD44, ICAM1, SNAI1, SNAI2, TNFRS11B)- and CSC (ABCG2, OCT4, Nanog, Musashi)-related mRNAs (Fig. 4E ), all shown to contribute a clonogenic, chemo-resistant phenotype in MPM and other solid tumors [ 40 , 41 ]. Finally, we found increased mRNA of enzymes involved in downstream processing of AA, namely PGES, PTGIS, COX1 and COX2 [ 42 ](Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Such subpopulations are often endowed with stemness properties and are referred to as cancer stem cells. More specifically in breast cancer, CSCs have been described as manifesting remarkable resistance to standard treatments [58,59], making them prime candidates for the development of novel, targeted therapies that could be administered in combination with commonly used drugs, aiming to achieve complete tumor elimination [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein 1 (Pgp-1), also known as ATP-binding cassette subfamily B member 1, functions as a transmembrane efflux pump involved in the chemotherapy drug uptake and its efflux. Overexpression of aldehyde dehydrogenase-1 (ALDH-1) in breast cancer was also found to be correlated with the stemness features of CSCs [100][101][102]. The findings from a recent report have suggested that cotreatment of CUR and PTX inhibited the ALDH-1 and PTX-induced Pgp-1 expression in MCF-7 cells.…”
Section: Curcumin Enhances the Efficacy Of Paclitaxel In Breast Cance...mentioning
confidence: 98%